Haploidentical hematopoietic stem cell transplantation for paediatric high‐risk T‐cell acute lymphoblastic leukaemia. (20th March 2016) - Xu, Zheng‐Li; Huang, Xiao‐Jun; Liu, Kai‐Yan; Chen, Huan; Zhang, Xiao‐Hui; Han, Wei; Chen, Yu‐Hong; Wang, Feng‐Rong; Wang, Jing‐Zhi; Wang, Yu; Chen, Yao; Yan, Chen‐Hua; et al.
Abstract: Paediatric HR T‐cell ALL demonstrates dismal prognosis with chemotherapy, and poor outcomes could be improved with allo‐SCT. HID‐SCT is an almost immediately available choice; however, few studies have focused on the outcomes of HID‐SCT for paediatric HR T‐ALL. Forty‐eight consecutive HR T‐ALL children who underwent HID‐SCT were included. Survival outcomes and factors predictive of outcomes were retrospectively analysed. Of the 48 patients, 35 were in CR1, 10 in CR2, and three in relapse. The cumulative incidence of grade 3/4 aGVHD was 10.4% and that of extensive cGVHD was 28.4%. The CIR at three yr was 30.8% and that of NRM at three yr was 14.7%. At a median follow‐up of 20.0 (range 2.5–124.2) months, the three‐yr LFS was 54.4%. Children who received transplants during CR1 had a better LFS (65.7% vs. 26.0%, p = 0.008) and a lower relapse rate (19.8% vs. 56.7%, p = 0.014) compared to those during non‐CR1. HID‐SCT is feasible for HR T‐ALL children, and survival outcomes are better when performed in CR1 compared to non‐CR1. Prospective clinical trials would be needed to confirm that.